When Crohn’s ileitis is not just ileitis (Revista Argentina de Cirugía, 2022)
In a minority of patients with long-standing Crohn’s ileitis, the recrudescence of symptoms may represent a neoplasm involving the ileum that is clinically indistinguishable from the baseline disease and therefore poorly suspected. Tumors are often diagnosed in the surgical specimen, after an intervention due to bleeding or bowel obstruction.The aim of this study is to emphasize the importance of the differential diagnoses of terminal ileitis in a patient with CD with poor response to medical treatment.
Keywords: Crohn’s disease; ileitis; small bowel obstruction; small bowel cancer